Study of the perception of open data by Colombian public entities (2019)
The worldwide use of open data has had impact on governments on a global scale, in how information is published and treated. The objective of this article is to investigate the perception of officials in public entities regarding the status of open data in Colombia., in addition to which countries are using them and how advanced are the generation and disclosure of information. A survey was performed on different public entities in Colombia to determine the problems, strengths and opportunities of open data, as well as the difficulties faced by public entities when posting. These results gave a perspective on the symptoms of public entities and the actions that the government can take.